Dynamics of Three and Four Non-identical Josephson Junctions - Kuznetsov, Alexander P.; Sataev, Igor R.; Sedova, Yuliya V. (Journal of Applied Nonlinear Dynamics, 2026)
Dynamics of chains of three and four coupled non-identical Josephson junctions is considered. Synchronization effects are discussed including resonance Arnold web formation on the base of tori of different dimensions.